Media Grafis Kartu Pada Materi Menghargai Jasa dan Peranan Tokoh Untuk Meningkatkan Hasil Belajar Ips Siswa Kelas V - Sumarni Sumarni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
The grade V students at SDN 07 Ulakan Tapakis had low attention in social subject learning. It caused their learning achievements came low too. We thought that using graphic media is one of its solutions. Graphic media is a kind of visual media called 2-D media.This is a classroom action research with two cycles. This study is aimed to improve students’ learning achievement in social subject. Students got average score of 63.70 in pre cycle. In cycle I, students’ average score becomes 68.04 but it is still not satisfied. In cycle II, students’ average score improve significantly, i.e. 81.56. Thus, implementation of graphic media can improve the student’s learning achievement in social subject.